2017
DOI: 10.1186/s12960-017-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

The current situation of human resources for health in the province of Cabinda in Angola: is it a limitation to provide universal access to healthcare?

Abstract: BackgroundAngola is among sub-Saharan African countries dealing with a crisis of Human Resources for Health (HRH). The province of Cabinda, besides the efforts, still suffers from both HRH shortage and a badly distributed health workforce. In Cabinda, one can find urban concentration and rural shortages of healthcare professionals, many rural areas’ healthcare facilities often secured only by basic or medium level HRH; and difficulties in developing HRH retention strategies in rural areas where most services a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, the densities of the nurses in all three regions in our study were lower than the density reported from Angola. The study in Angola also shows a higher density of nurses in rural than in urban areas [40]. The median of midwives per 10,000 inhabitants in rural areas of Dire-Dawa were about twice (p = 0.016) that of the urban area.…”
Section: Discussionmentioning
confidence: 98%
“…However, the densities of the nurses in all three regions in our study were lower than the density reported from Angola. The study in Angola also shows a higher density of nurses in rural than in urban areas [40]. The median of midwives per 10,000 inhabitants in rural areas of Dire-Dawa were about twice (p = 0.016) that of the urban area.…”
Section: Discussionmentioning
confidence: 98%
“…Angola is among the sub-Saharan African countries dealing with a crisis of Human Resources for Health (HRH) (Craveiro & Dussault, 2016). Only the populations living in large towns, such as Luanda and other provincial capitals, have access to health facilities and the medicinal plants are still widely used across the country, as they are effective, cheap, used for cultural reasons, and readily available (Macaia & Lapão, 2017). Thus, priority should be given to initiatives for preventing the loss of local knowledge in this country, and for identifying relevant gaps with regard to the conservation and sustainable use of the medicinal plant diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of the rationales behind health workers’ decision to transfer is important, as it provides an insight into why health workers seek to leave their facility. Poor retention of health workers is a significant problem in rural and remote areas, with negative consequences for the delivery of high-quality health services [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…A main challenge in HR management is to integrate the needs of the organization with the individual needs of its members [30]. Nevertheless, successful attempts have been made, for example in Zambia, where financial incentives have been successfully applied to motivate health worker transfers to rural areas [18, 22]. The potential of non-monetary incentives has also been demonstrated, i.e., career development, appropriate accommodation, clear terms of appointment with a reliable endpoint, and provisions for the schooling of children [19–21, 3133].…”
Section: Discussionmentioning
confidence: 99%